Poverty and HIV/AIDS in South Africa: an empirical contribution - Lerato Sonia Tladi (Taylor & Francis Group, 2006)
This study sets out to establish and explain the empirical link between HIV/AIDS and poverty using data collected by the 1998 South African Demographic and Health Survey (SADHS). Analysis is restricted to women of reproductive age (15 - 49 years). The results indicate an increased risk of HIV infection among the poor, due to poverty-related characteristics of low education and low knowledge of the means of avoiding HIV infection, as opposed to the non-poor. Moreover, the poor and the less educated were found to be more likely not to use condoms than the non-poor. The results do not, however, provide the reasons for these relations and as such further research is required. One possible explanation was financial dependence on their partners, as it was found that women who received money from their partners, as well as those who came from households where hunger was a common phenomenon, were more likely not to use condoms because their partners disliked condoms, than those who did not receive money from their partners. The results also hinted at the intricacy of the poverty-HIV/AIDS relationship, so that it was not only low socio-economic status that increased susceptibility to HIV infection but also high socio-economic status.